Analisis Hubungan Keterampilan Proses Sains dan Kemampuan Literasi Sains Peserta Didik Kelas VIII SMPN 18 Makassar - Nirwana Nirwana; Muh. Tawil; Muhammad Danial (Universitas Negeri Makassar, 2026)
This study aims to: (1) Describe how high the level of science process skills of grade VIII students of SMPN 18 Makassar, (2) Describe how high the level of science literacy ability of grade VIII students of SMPN 18 Makassar, (3) Describe the significant relationship between science process skills and science literacy ability of grade VIII students of SMPN 18 Makassar. This study is descriptive correlative with the population of all grade VIII students of SMPN 18 Makassar which amounted to 296 while the sample amounted to 171. The instruments used are science process skills tests and science literacy ability tests on light matter and optical instruments in the form of multiple choice. The data were analyzed with descriptive statistics and inferential statistics. The results of the study obtained the science process skills of grade VIII students of SMPN 18 Makassar were in the low category with an average score of 8.80, the science literacy ability of grade VIII students of SMPN 18 Makassar is in the low category with an average score of 7.11 and there is a significant relationship between science process skills and science literacy ability of grade VIII students of SMPN 18 Makassar with pearson correlation of 0.458 which is included in the medium category.